Role of Common-Gamma Chain Cytokines in NK Cell Development and Function: Perspectives for Immunotherapy. (13th June 2011) - Meazza, Raffaella; Azzarone, Bruno; Orengo, Anna Maria; Ferrini, Silvano
Abstract : NK cells are components of the innate immunity system and play an important role as a first-line defense mechanism against viral infections and in tumor immune surveillance. Their development and their functional activities are controlled by several factors among which cytokines sharing the usage of the common cytokine-receptor gamma chain play a pivotal role. In particular, IL-2, IL-7, IL-15, and IL-21 are the members of this family predominantly involved in NK cell biology. In this paper, we will address their role in NK cell ontogeny, regulation of functional activities, development of specialized cell subsets, and acquisition of memory-like functions. Finally, the potential application of these cytokines as recombinant molecules to NK cell-based immunotherapy approaches will be discussed.